1993
DOI: 10.1038/365664a0
|View full text |Cite
|
Sign up to set email alerts
|

ATP-induced protein Hsp70 complex dissociation requires K+ but not ATP hydrolysis

Abstract: The molecular chaperone proteins, particularly Hsp60 and Hsp70, have been implicated in essential cell functions under both normal and stress conditions (reviewed in refs 1-5). Members of the family of heat-shock proteins of M(r) 70K, Hsp70, bind to unfolded proteins and short peptides. Addition of Mg-ATP results in the dissociation of the substrate polypeptides from the chaperone, but as ATP-gamma S (an ATP analogue that is only slowly hydrolysable) cannot substitute for ATP in this reaction, it has been conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
296
3
3

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 384 publications
(327 citation statements)
references
References 19 publications
25
296
3
3
Order By: Relevance
“…In vitro studies have shown that Hsp70/DnaK proteins bind both denatured proteins and some short peptides, and release these substrates in response to the addition of ATP [47,48]. Hsp70/DnaK proteins have a weak ATPase activity and a peptide binding activity with a mechanism of coupling these two activities such that the addition of ATP induces peptide release [5,49]. The open/closed state of the Hsp70/ DnaK substrate-binding domain, which is mediated by the repositioning of a α-helical lid over the substrate-binding pocket, is governed by the nucleotide occupancy and status in the ATPase domain [5,50].…”
Section: Secondary Structure Of Bldnakmentioning
confidence: 99%
“…In vitro studies have shown that Hsp70/DnaK proteins bind both denatured proteins and some short peptides, and release these substrates in response to the addition of ATP [47,48]. Hsp70/DnaK proteins have a weak ATPase activity and a peptide binding activity with a mechanism of coupling these two activities such that the addition of ATP induces peptide release [5,49]. The open/closed state of the Hsp70/ DnaK substrate-binding domain, which is mediated by the repositioning of a α-helical lid over the substrate-binding pocket, is governed by the nucleotide occupancy and status in the ATPase domain [5,50].…”
Section: Secondary Structure Of Bldnakmentioning
confidence: 99%
“…One well known and carefully studied function of molecular chaperones involves refolding of denatured proteins to their native form. The process is gradual and involves repeated, cation-dependent cycles of associationdissociation (5,12,13). It is possible that Hsc70 is involved in an attempt to refold denatured proteolytic substrates.…”
Section: Possible Mechanism Of Involvement Of Hsc70 In Ubiquitinmediamentioning
confidence: 99%
“…1 and Table II). In a search for a potential role of the cations in the proteolytic process, we noted that several functions of the 70-kDa heat shock cognate protein (Hsc70), such as peptide binding and release and clathrin uncoating, require K ϩ (12,13,41). The cation is required, most probably, to allow the change in the conformation of the chaperone that is necessary for substrate dissociation.…”
Section: Effects Of Cations On the Degradation Of Certain Proteinmentioning
confidence: 99%
See 2 more Smart Citations